HYGIENIC ASSESSMENT OF FOOD PRODUCTION ENTERPRISES AS A SOURCE OF POLLUTION OF ATMOSPHERIC AIR - Sultonov, Erkin; Murodullayev , Malikshox; Murodullayev , Mironshox (Educational Research in Universal Sciences, 2023)
Food production is a vital aspect of modern society, ensuring the sustenance of populations globally. However, the processes involved in food production, if not managed with careful consideration, can contribute to environmental challenges. This article delves into the hygienic assessment of food production enterprises, shedding light on their potential role as a source of atmospheric air pollution. The assessment explores various aspects, including waste disposal, emissions, and manufacturing practices, to evaluate their impact on air quality. By scrutinizing the hygienic conditions of these enterprises, the article aims to raise awareness of the environmental implications associated with food production. Understanding and mitigating these impacts are crucial steps toward sustainable and eco-friendly practices in the food industry.